BUSINESS STRATEGY, KNOWLEDGE MANAGEMENT DAN CORPORATE SOCIAL PERFORMANCE DALAM MEMPENGARUHI ECONOMIC PERFORMANCE - Arry Eksandy; Riski Ulan Sari; Vianty Dewi Rengganingsih (COMPETITIVE, 2020)
This research aims to determine the effect of business strategy, knowledge management and corporate social performance on economic performance partially on companies manufacture during the period 2014-2018.The population in this research is all companies manufacture listed on Indonesia Stock Exchange during the period 2014-2018. The total samples tested were 15 companies selected by purposive sampling technique. Data type in this research use secondary data obtained from Indonesia Stock Exchange and site respectively of company being sampled. Data analysis technique use panel data regression with Eviews 9.0 program.The result indicates that business strategy have no effectt on economic performance. Knowledge Management have a positive effect on economic performance. And Corporate Social Performance have no effect on economic performance.